Fenntarthatóság és növekedés: A Stern jelentés és az irányított technológiaváltás modellje - Edina Berlinger; Anita Lovas (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
– In this paper we investigate the relationship between sustainability and economic growth starting from Stern (2006) which is the first comprehensive analysis of the global warming from economic point of view. We also discuss the critical debate of this study which was focused mainly on the proper selection of the social discount rate. Then we present Acemoglu et al. (2012) which provides a generalized framework to understand the problem. In this model, called directed technical change, innovation is a key driving factor and contrary to the Stern review, it is endogenous. Interestingly, in this setting, the social discount rate becomes irrelevant. Finally, we also summarize the new developments related to the right parameter setting and the role of the state to manage the most significant negative externality of the planet.
Keywords: G18; H23; O33; Q56; 330; sustainability; growth; Stern review; endogenous innovation; directed technical change; negative externalities; role of state